Prevalence of methicillin-resistant Staphylococcus aureus in milk and dairy products - PEXARA (Α. ΠΕΞΑΡΑ), A.; SOLOMAKOS (Ν. ΣΟΛΩΜΑΚΟΣ), N.; GOVARIS (Α. ΓΚΟΒΑΡΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Staphylococcus aureus is an opportunistic Gram positive pathogen and the causative agent of many human and animal diseases. It is also an important human foodborne pathogen. Certain strains of S. aureus can produce staphylococcal enterotoxins (SEs) in foods and cause staphylococcal food poisonings (SFP). In recent years S. aureus has been increasingly associated with antibiotic resistance. Methicillin-resistant S. aureus (MRSA) includes those strains that have acquired genes conferring resistance to methicillin and essentially all other beta lactamantibiotics. MRSA was initially reported as a nosocomial pathogen in human hospitals (or hospital-associated MRSA, HA-MRSA). Since the 1990s, community-acquired or community-associated MRSA (CA-MRSA) infections have also been reported to affect people having no epidemiological connection with hospitals. More recently, MRSA has been isolated from most food-producing animals and foods of animal origin, raising public health concerns. MRSA strains have been isolated from cows’ or small ruminants’ milk and various dairy products in many countries. The MRSA prevalence in milk and dairy products recorded in different countries or even regions of the same country differs significantly. High MRSA prevalence have been recorded in milk produced in most African countries, for instance as high as 60.3% in Ethiopia. The MRSA prevalence in Asian countries varies from high e.g. 28.3% in Iran to low (e.g. in Korea and Japan). In most European countries, the MRSA prevalence in milk and dairy products has been generally found to be low. In the US and Canada, zero to low MRSA prevalence estimates have been reported. The investigation of MRSA prevalence in milk may serve as a tool for assessing both the sanitary conditions employed in dairy herds and the health risks that humans may encounter when infected with antibiotic-resistant strains.